Success, challenges and prospects of decentralization in Africa: a systematic review - Rogers Rugeiyamu; Adam Msendo (Cogent Social Sciences)
Decentralization remains a global development approach. African countries have been using decentralization by devolution to realize their development vision. This study assesses the success, challenges, and prospects of decentralization in Africa. The results reveal that there has been considerable success of decentralization in African countries. Success relates to setting political structures at the local level, conducting elections, strengthening the budgetary system, and improved service delivery. Decentralization faces many challenges related to policy, legislation, and the lack of political will, limited autonomy, and overdependence on central government. This has been caused by the fact that rather than implementing devolution, African countries have been implementing deconcentration, a thing which is caused by the unitary nature of governments. Impliedly, the existing theory of decentralization is not properly working in Africa. Thus, the prospects of decentralization require policy and legislation changes and proper implementation, granting local authorities autonomy to administer development based on their priorities and capacitating local authorities to be accountable, responsive, and implement inclusive development. This would ensure the internalization of decentralization as a developmental approach in Africa. The study limited itself to secondary materials, more studies are recommended to capture the opinion and experiences of local government actors on decentralization.